Improvising with Technology: Phenomenology, Pedagogy, and Performance - De Souza, Jonathan (Critical Studies in Improvisation / Études critiques en improvisation, 2026)
In this article, I approach improvisation and technology via a network of concepts instead of binary oppositions, emphasizing reciprocity instead of hierarchy. This line of thinking is inspired by phenomenological approaches to technology, which I review in Part 1. Part 2 examines case studies related to performance, while Part 3 turns to pedagogical uses of improvisation. Across these contexts, I argue that improvisation has no single origin but emerges from the interplay of bodies and technologies that are situated in a world.